2017
DOI: 10.24925/turjaf.v5i13.1716-1520.1519
|View full text |Cite
|
Sign up to set email alerts
|

Yield and Quality Features of Buckwheat-Soybean Mixtures in Organic Agricultural Conditions#

Abstract: This study was carried out during the summer of 2014 to determine alternative quality forage sources that could be grown in the Aydın ecological conditions. In the study, effects of 3 different mixtures and 2 pure species (100% Buckwheat, 25% Buckwheat -75% Soybean, 50% Buckwheat -5 0% Soybean, 75% Buckwheat -25% Soybean, 100% Soybean) and 2 different harvesting times (50%-100% flowering/buckwheat) on yield and quality characteristics were investigated. According to measurements, the highest average herbage yi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 2 publications
0
6
0
1
Order By: Relevance
“…For instance, Kara (2014) reported that dry matter yield in buckwheat varies year to year and increases approximately 6.3 times from the beginning of flowering to the period at which 50% of the grains have turned brown. Surmen and Kara (2017), on the other hand, reported that in Aydın's ecological conditions, the dry matter yield of pure buckwheat was 5497.5 kg ha -1 at 50% flowering period and 5085.2 kg ha -1 at 100% flowering period. The dry matter yields obtained in our research were lower than the yields obtained in previous studies on this subject.…”
Section: Dry Matter Yieldmentioning
confidence: 98%
See 3 more Smart Citations
“…For instance, Kara (2014) reported that dry matter yield in buckwheat varies year to year and increases approximately 6.3 times from the beginning of flowering to the period at which 50% of the grains have turned brown. Surmen and Kara (2017), on the other hand, reported that in Aydın's ecological conditions, the dry matter yield of pure buckwheat was 5497.5 kg ha -1 at 50% flowering period and 5085.2 kg ha -1 at 100% flowering period. The dry matter yields obtained in our research were lower than the yields obtained in previous studies on this subject.…”
Section: Dry Matter Yieldmentioning
confidence: 98%
“…Björkman and Chase (2017) determined that the crude protein ratio in buckwheat varies between 15 and 20 % prior to flowering and that these values later decrease to 9 % depending on maturity. Surmen and Kara (2017) reported that in Aydın's ecological conditions, the crude protein rate in pure buckwheat was 15.89 % in the 50 % flowering period and 13.56% in the 100 % flowering period. In our study, the crude protein ratios measured during the flowering stage were higher.…”
Section: Crude Proteinmentioning
confidence: 99%
See 2 more Smart Citations
“…Farklı zamanlarda ekilen karabuğday çeşitlerinin SKM ve KMT oranlarına ait ortalama değerler Konya koşullarında %59,20-68,68[17] olarak elde edilen bu bulgular, çalışma sonucundan alınan verilerden yüksek olduğu tespit edilmiştir. Tabloya bakıldığında, ekim zamanı açısından incelendiğinde en yüksek KMT oranı %2,77 ile 1. ekim zamanında görülürken, bunu istatistiksel bakımından aynı grupta yer alan 3. ekim zamanı (%2,75) takip etmiştir.…”
unclassified